Ojciec Wacław Szuniewicz – polski misjonarz, okulista, prekursor chirurgii refrakcyjnej rogówki - Bieganowski, Lech (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
The article presents the life and work of Polish missionary of Saint Vincent a Paulo order, an ophthalmologist, Father Wacław Szuniewicz. He was born in 1891 in the Vilnius region. He completed his medical studies in Moscow in 1916. He specialised in ophthalmology at Stefan Batory University in Vilnius. In 1927 he entered the missionaty order and after being ordained n 1930, he was sent for mission to China. There he developed his involvent in ophthalmology and established the ophthalmic ward in Shuntehfu that became very renowned. After taking over by the communist in China, he went to US in 1948. He continued his experimental work on surgical method on changing corneal curvature at Yale University in New Haven. In 1952 he went to Brasil where he continued his work as a missionary and an ophthalmologist. He was a man of great kindness and knowledge. He had particular language skill. At high school and during his medical and theological studies, he mastered Russian, French, English, Latin and Hebrew. He also learnt Chinese and Portugese. He was able to communicate in Lithuanian and Byelorus. He died in Brazil on 16 october 1963. His scientific accomplishments make him one of the pioneers of refractive surgery of cornea.